FAKTOR - FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA PERBANKAN SYARIAH DI INDONESIA - FIRDA AMALIA, (2021)
The research conducted by researchers aims to determine the influence of sharia banking performance on the absorption of sharia banking labor in Indonesia. In this study, researchers wanted to measure the absorption of labor in Sharia banking based on sharia banking performance. This study uses a quantitative approach with the research population of Sharia Commercial Banks in Indonesia and this research sample is a statistical report of Sharia banks in Indonesia in 2014 - 2019. The data source used in this study is secondary data derived from books, documentation, journals, written web sites related to the object of this research through OJK, BPS, Bank Indonesia and each Sharia Commercial Bank. Testing the data using regression of panel data is expected to provide the advantage to be able to detect and measure the impact well. The results of this study were on variables ROA, ROE, CAR and NPF have a significant influence on the absorption of labor, while FDR does not have a significant influence on the absorption of labor.